Duality of osculating developables of projective curves - Hefez, Abramo; Kakuta, Neuza [UNESP] (Taylor & Francis, 2001)
We give a description of the dual varieties of all developables of osculating linear spaces to a projective curve in terms of the higher order dual varieties of the curve, in arbitrary characteristic. We also determine for these varieties the inseparable degrees of the projections from the conormal varieties onto their dual varieties.
Keywords: Osculating developables; Projective curves; Projective duality